External Assurance and Subsequent ESG Performance: Examining Firm Visibility and Female Director Representation - Anita Anita; Mavrict Josephino; Handoko Karjantoro (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2026)
Purpose - This study examines whether external assurance is associated with corporate environmental, social, and governance (ESG) performance in the assurance year and the subsequent year. It also investigates whether firm visibility and female director representation strengthen the relationship between external assurance in the preceding year and subsequent ESG performance. Research Method - The study employs an unbalanced panel of 89 companies listed on the Indonesia Stock Exchange from 2019 to 2023. The dataset comprises 318 firm-year observations, while the subsequent-period analysis uses 229 observations because assurance information must be available for the immediately preceding year. ESG performance is measured using the Refinitiv ESG Score. Assurance, governance, ownership, and financial data are manually collected from annual and sustainability reports. The hypotheses are tested using ordinary least squares regressions with industry and year fixed effects and heteroskedasticity-robust standard errors. Findings - External assurance is positively and significantly associated with ESG performance in both the assurance year and the following year. Firms obtaining assurance in the preceding year tend to report higher subsequent ESG scores, supporting the proposed temporal relationship. However, firm visibility and female director representation do not significantly moderate this association. Implication - The findings suggest that external assurance may contribute beyond reporting credibility by supporting improvements in ESG data systems, internal controls, monitoring, and organizational practices. Companies should therefore treat assurance as a mechanism for learning and performance improvement. Regulators and boards should place greater emphasis on assurance quality, engagement scope, provider competence, and management follow-up in emerging capital markets including Indonesia.